2021
DOI: 10.3390/ijerph18137101
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mobile Phone Use on Driving Performance: An Experimental Study of Workload and Traffic Violations

Abstract: The use of communication technologies, e.g., mobile phones, has increased dramatically in recent years, and their use among drivers has become a great risk to traffic safety. The present study assessed the workload and road ordinary violations, utilizing driving data collected from 39 young participants who underwent a dual-task while driving a simulator, i.e., respond to a call, text on WhatsApp, and check Instagram. Findings confirmed that there are significant differences in the driving performance of young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…2. The projected data does not always distract the driver, as mobile phones or dashboard controls may do [37,12]. 3.…”
Section: Safety Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…2. The projected data does not always distract the driver, as mobile phones or dashboard controls may do [37,12]. 3.…”
Section: Safety Aspectmentioning
confidence: 99%
“…On the other hand existing experiments have shown that receiving a call may cause an accident because it delays visual information processing by the driver. This benefit of Head-Up windshield should therefore be taken in quotation marks [10][11].…”
Section: Introduction Of Head-up Displaysmentioning
confidence: 99%
“…Globally, there are 5.27 billion unique mobile phones today, representing 66.9% of the total population [ 34 ]. The ubiquity of smartphones is undoubted, affecting the driving process, and represents a significant public health threat [ 35 , 36 ]. Talking on the phone while driving (TPWD) can have a wide range of unfavorable consequences [ 37 , 38 ], and contribute to the number of distraction-affected crashes [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…As per the statistics presented by the World Health Organization (WHO), road injuries are one of the top 10 leading causes of death in upper-middle-income countries like India. Almost 80-90% of traffic accidents are caused by the driver's mistakes while operating the vehicle, as well as a lack of attention and distracted behavior [25]. Due to this, countries all around the world are giving it an extremely high priority to improve road safety and develop a better traffic management system.…”
Section: Introductionmentioning
confidence: 99%
“…Even though there are multiple potential contributing factors, a lot of experiments indicate that the usage of a cellular phone while driving is likely to cause an accident as it delays the visual information processing by the driver [17]. Distracted driving, as it is well established in the literature, takes drivers' eyes off the road, switches their consciousness from driving to other tasks, and results in false perceptions [25]. Thus, in this project, we have proposed a vision-based solution that will warn the driver with an alerting sound when he or she is found with a mobile device in their hand [16].…”
Section: Introductionmentioning
confidence: 99%